Punicalagin attenuated allergic airway inflammation via regulating IL4/IL-4Rα/STAT6 and Notch- GATA3 pathways - Yu Li; Li Jianying (Acta Pharmaceutica, 2022)
Allergic asthma is an inflammatory disease of the airways which has a complex etiology. Punicalagin, a major polyphenol present in pomegranates, is reported to possess various biological properties including antioxidant and antiproliferative effects. The current research aimed to evaluate the antiasthmatic effects of punicalagin in an ovalbumin (OVA)-induced experimental model of asthma in female BALB/c mice. Treatment group animals received punicalagin (12.5, 25 or 50 mg kg−1 body mass) per day for 21 days from day 1 of OVA injection. Dexamethasone (DEX) was administered to a separate group of mice, as the standard drug control. Inflammatory cell infiltration into the broncho-alveolar lavage fluid (BALF) was substantially decreased in punicalagin-treated mice. Punicalagin reduced Th2-derived cytokines and OVA-specific IgE levels. The IL-4/STAT6 and Notch/GATA3 signalling pathways were regulated on punicalagin administration. The data obtained illustrate the potency of punicalagin as an anti-asthmatic drug. Conclusively, the study’s observations suggest the potential therapeutic efficiency of punicalagin in allergic asthma.